Pengaruh Kontrol Diri Terhadap Perilaku Konsumtif Peserta Didik Kelas XI di SMAN 2 Merangin - Humaira Kamala; Rici Kardo; Suryadi Suryadi (Departement of Mathematics Education, 2023)
This research is motivated by the effect of self-control on consumptive behavior of students of SMAN 2 Merangin class. The research objective is to describe; 1) To find out the consumptive behavior of class XI students of SMAN 2 Merangin, 2) To find out the self-control of class XI students of SMAN 2 Merangin, 3) To determine the effect of self-control on consumptive behavior of class XI students of SMAN 2 Merangin. This research is a type of quantitative descriptive research with a simple linear regression analysis approach. This study collected data using observation, questionnaires and documentation. The population of this study were all 141 students of class XI at SMAN 2 Merangin. The sampling technique used purposive sampling technique as many as 66 people. The instrument used is a questionnaire. Data analysis using percent technique. The results of this study reveal that, R Squalre X at Y 0.123, it can be concluded that self-control is identified as having an influence, namely 0.123 x 100%, so the effect of X on Y is 0.123%, while the rest is influenced by traffic variables that were not detected by researchers . researchers do this. Then the hypothesis is accepted which states that there is a significant influence of self-control variables on consumptive behavior.